Effects Of Environmental Factors And Atmospheric Pollution in the Incidence of Hospital Admissions of Patients With Stroke In São Paulo City By Stroke In São Paulo City - Ramos Takahashi, André Akira; Corral Ponce, André Costa; Maria Bezerra, Italla; Antonio Correa, João; Werneck de Carvalho, Luis Eduardo; Daminello Raimundo, Rodrigo; Silva Paiva, Laércio da; Luiz Affonso Fonsec, Fernando; Carlos de Abreu, Luiz Carlos de Abreu; Alcantara Sousa, Luiz Vinicius de Alcantara Sousa; Adami, Fernando (European Scientific Journal, ESJ, 2022)
Introduction: Stroke is one of the major causes of morbidity and mortality worldwide, difficult to treat and recover. The risk of developing stroke may be associated with environmental factors. Objective: To analyze the association between ambient temperature, air humidity and atmospheric pollution with the incidence of hospital admissions for stroke in the city of São Paulo in 2016. Methods: This is an ecological study, carried out by secondary data collection in the city of São Paulo in 2016. The definition of Stroke was according to the tenth revision of the International Classification of Diseases in codes: I60, I61, I63 and I64. Results: There was a positive correlation between the incidence of hospital admissions for stroke and in SO2 in air (rho: 0.80, p=0002) in women. In men there was a positive correlation between the number of hospital admission and SO2 concentration (rho: 0.570, p=0.005). Conclusion: We observed a positive correlation between the incidence of stroke and the concentration of the atmospheric pollutant SO2, an important fact for the intervention in the dispersion of pollutants.